The Role of the International Auditing Standard Quality Control for Auditing Financial Statements (220ISA) in Narrowing the Expectations Gap :: An Exploratory Study of the Opinions of a Sample of Certified Accountants and Auditors in the Kurdistan Region - ابراهيم دريا حربي; عبدالله شيخ د.ارشد صديق (Polytechnic Journal of Humanities and Social Sciences, 2023)
This study aimed, in its theoretical and practical aspects, to demonstrate the existence of the reasons for the expectations gap in the Kurdistan Region / Iraq and the extent of the role of compliance with the International Auditing Standard (ISA 220) related to quality control for auditing financial statements in narrowing them from the point of view of certified accountants and auditors in the Kurdistan Region / Iraq, and to achieve the objectives In this study and testing its hypotheses, a questionnaire consisting of three axes was prepared and distributed to certified accountants and auditors in the Kurdistan Region / Iraq. The results were analyzed using the statistical package for social sciences (SPSS) program. The study reached a set of conclusions, most notably: The study emphasized the existence of reasons for the audit expectations gap in the environment of the Kurdistan Region / Iraq, as the results of the analysis confirm that the existence of the gap in the region is the result of deficiencies in local laws and legislation in the region according to the sample answers, and this is what affect the performance of the audit process. The results of the analysis using the correlation coefficient and the regression equation indicated that there is a significant positive linear correlation of (77.6%) between the (ISA 220) standard and the narrowing of the expectations gap in the current study, which has a relationship and a high significant impact in narrowing the expectations gap that can be adopted and developed in order to narrow the expectations gap. . Among the most important recommendations of the study: the need for professional organizations to study and analyze the expectations gap in the auditing environment and work on applying the best proposals to address them or narrow them down to a minimum, because it is considered one of the most serious issues facing the auditing profession at the present time, which directly affects the credibility and quality of the financial statements and the decisions of its users. Financial Statements. And the need to form a committee by the authorities responsible for regulating the auditing profession, especially from the Scientific Association of Accountants and the Association of Accountants and Auditors in the region’s environment, to supervise audit quality control to ensure that audit offices apply the audit quality control system in order to narrow the expectations gap.